10. CRANIAL NERVE XII PALSY AFTER SHOULDER ARTHROSCOPY UNDER BEACH CHAIR POSITION: A CASE REPORT (Vietnam Journal of Community Medicine, 2025)
Compared to the lateral decubitus position, shoulder arthroscopy performed in the beach chair position offers superior surgical field exposure, reduces the risk of brachial plexus injury due to traction, and facilitates conversion to open surgery or airway access when necessary. Despite these advantages, beach chair position related to some inherent risks, including hemodynamic instability associated with positional changes. Although cranial nerve palsies following beach chair position surgeries rarely happens, particularly hypoglossal nerve (cranial nerve XII) injury, it is clinically significant and warrant careful consideration. We report a case of a 76-year-old female patient with no underlying medical conditions who underwent arthroscopic rotator cuff repair and subacromial decompression in the beach chair position under general anesthesia. Postoperatively, the patient developed dysarthria and left-sided tongue deviation. Neurological examination confirmed symptoms consistent with left hypoglossal nerve palsy. Brain MRI revealed no focal lesions. The patient received conservative medical management combined with speech rehabilitation, resulting in complete recovery within 12 weeks.Keyword: Shoulder arthroscopy, cranial nerve XII, beach chair position.
Keywords: Shoulder arthroscopy, cranial nerve XII, beach chair position.